ENGLISH TEACHING-LEARNING PROCESS USING GAMES AT "PERMATA HATI" PLAY GROUP WONOGIRI - PURNAMAWAT, LAIL (2007)
The objectives of this research are to describe the English teaching-learning processusinggames and also the strengths and the weaknesses of it. Thisresearch was undertaken in Permata Hati Play group Wonogiri. The subjects of the research are the teacher and the group B (Bulan) students of Permata Hati Play Group. There were 21 students in group B. The writer collected the data of the research through observation, field notes, and interview. The result of the data analysis shows that in teaching-learning process the teachers always opened with greeting, then continued by classroom activities such as games, and the last is closed by greeting. In the classroom the teachers and the student show a good interaction. There is a cheerful circumstance. The children followed the classroom activities enthusiastically and if the children get difficulties the teachers always help them. There were also some strengths and the weaknesses of English t eaching- learning process using games. Those strengths are the teacher was behaving energetically, clearly, encouragingly, and fairly. In games, the children also have a high interest in following the activities, they were motivated to be active and to compete fairly, they could learn while playing, and the circumstance is relaxed, cheerful and enjoyable. Besides that, all of the children had opportunity to be active in the following the games. The weaknesses of games are the teachers need an extra energy, n eed an extra patience to handle the children during the games, and the teachers always help and guide the children continually. Besides that games are also a time consuming activities. In doing the games some of the children are not serious and easily felt bored. The writer concludes that the English teaching-learning process using games at Permata Hati Play Group runs well. Although the English subject is not the part of curriculum from the institution but the classroom activities are effective. The children can absorb the materials well and have a good result.